Implementation of Social Media for Marketing of The Jungle Waterpark, Bogor - Nugraha, Rizki Nurul; Dewi, Liliana; Sarinah, Lisa (Westscience Press, 2024)
Social media today is an important part of business, to be used as a medium for marketing their products and also to reach a wider target market. The Jungle Waterpark located in Bogor, West Java, Indonesia, is a water park that offers many attractions and adequate facilities. This research aims to explore how The Jungle Waterpark utilizes social media as their marketing strategy. This type of research is qualitative, using qualitative descriptive analysis. Data collection was carried out by direct observation and data collection from social media accounts such as Facebook, Instagram, Twitter, TikTok, and YouTube owned by The Jungle Waterpark. The results showed The Jungle Waterpark makes excellent use of social media platforms. Their photo and video posts include, product promos, sharing information, interesting content, and much more. However, their YouTube social media account needs a better improvement, because some of the content on their YouTube account is not as updated as their other social media platforms.